Trabalhando com qualidade de vida: uma proposta de atuação de psicólogos clínicos em promoção de saúde no ambiente empresarial - Langoni, Claudia Lúcia Fernandes (2021)
The objective of this academic research was to analyze the impact that an intervention that promotes reflection on quality of life issues, carried out in a business environment, would cause self-satisfaction with the quality of life of a group of 15 employees of a medium-sized company, of a capital of the Southeast region of Brazil. Participants voluntarily responded to an invitation sent by the Human Resources department that followed the company's communication policies. The selection criteria were: to integrate the permanent staff and to be interested and available for participation. The research, outlined as a case study, used a qualitative approach. The Intervention involved the participants for eight months, in eight face-to-face meetings, distributed as follows: an initial individual interview, five Thematic Workshops on Quality of Life, a final individual interview and a group meeting to monitor results, ninety days after the end of the last workshop. Semi-structured interviews and the Quality of Life SelfAssessment Instrument - adapted (Bassani and Langoni, 2017) were used to investigate the level of self-satisfaction with the quality of life of the participants, in ten areas: physical, psychological, spiritual, social, leisure, professional, family, financial, affective and intellectual. This instrument, applied in the initial interview and in the follow-up meeting, allowed access to possible changes. During the workshops, activities and guided reflections, focused on the themes chosen by the group, sought to promote an effective commitment to the lifestyle chosen by each one and to promote transformative actions that broadened the degree of self-satisfaction. The analysis plan made it possible to understand the data collected, associated with the studies of Clinical Psychology in a business environment, with the themes of style and quality of life, based on Environmental Psychology. The results indicated that the average level of general self-satisfaction with the group's quality of life increased from 66% to 79%. The scope analysis confirmed the evolution in eight of the ten areas studied and the stability in two. The psychological scope was the one with the greatest evolution, varying from 56% to 72% of satisfaction. The testimonies collected at the results monitoring meeting confirmed the assessment and the benefits recognized by the participants. The results showed that the intervention effectively generated a positive impact on self-satisfaction with the quality of life of the participants and indicated a possible, useful and little-explored way of contributing to Clinical Psychology with health promotion in the workplace